PROFIL LIPID DENGAN KEJADIAN MORTALITAS PADA PASIEN INFARK MIOKARD AKUT DI RSUD PANEMBAHAN SENOPATI BANTUL TAHUN 2015 - Darussalam, Miftafu; Nofiyanto, Muhamat (MEDIA ILMU KESEHATAN, 2017)
BACKGROUND: Lipid profile is important as supporting data on heart patients. Lipid profile is a state of fat seen in the levels of total cholesterol, LDL, HDL, and triglycerides. Disorders of lipid metabolism characterized by an increase or decrease in blood plasma is called dyslipidemia. Dyslipidemia has a close relationship with the occurrence of atherosclerosis and Acute Myocardial Infarction (AMI) as one of the leading causes of death in industrialized countries and emerging economies. OBJECTIVE: To determine the relationship lipid profile with the incidence of mortality in patients with acute myocardial infarction in hospitals Panembahan Senopati Bantul in 2015. METHODS: This study used a descriptive exploratory design with data retrieval medical record in 2015 with a total of respondents 106 was done in Panembahan Senopati Bantul District Hospital. To analyze the data, the researchers used the Lamda test. RESULT: The results obtained were an association of mortality with total cholesterol by P: 0006 and the level of closeness strong (0647), LDL with P: 0009 and the level of closeness strong (0647), HDL with P: 0017 and the level of closeness is strong enough (0529), triglycerides P: 0003 and the level of closeness strong (0765) CONCLUSION: Mortality of AMI was statistically significant associated with total cholesterol, HDL, LDL, and triglycerides. Keywords: Acute Myocardial Infarction (AMI), lipid profile, mortality of AMI